Combined antihypertensive therapy in different types of obesity in postmenopausal women - V. V. Skibitskiy; S. V. Skibitskaya; A. V. Fendrikova (Медицинский совет, 2013)
The influence of combined antihypertensive therapy, including ACE inhibitor (ACEi) or Aliskiren, on the basic parameters of structural and functional state of the left ventricular (LV) myocardium in postmenopausal women with arterial hypertension (AH) and different types of obesity (abdominal and gluteofemoral) was evaluated.